(untitled) (Islamic Sciences Journal, 2023)
This research came under the title (The significance of the noun form of the command verb and its impact on legal rulings as examples from the verses of the Holy Qur’an). Formulas and their impact on legal rulings; Because the Holy Qur’an used many of these formulas to indicate the command of something, and the nature of the research required that I divide it into two chapters preceded by an introduction. And the terminology, and the second requirement showed the significance of the command and its meanings for fundamentalists, and the second topic mentioned in it the formula of the command verb’s noun and its impact on the legal rulings, and divided it into two requirements, in the first requirement I mentioned the command verb’s noun formulas contained in the Holy Qur’an, and the second requirement showed the command verb’s noun formulas and their impact on Sharia rulings in the Holy Quran, and concluded the research with the most important findings